Research Progress of Base Reducing Enzyme Responsive Prodrug System and Its Potential in Cancer Treatment - Fang, Yicheng (International Journal of Public Health and Medical Research, 2026)
The core dilemma of cancer treatment is to achieve tumor targeted delivery of chemotherapy drugs, reduce toxic and side effects on normal tissues, and improve the enrichment and activation efficiency of drugs in tumor sites. As a kind of oxidoreductase with high specific expression in tumor tissues and low or no expression in normal tissues, it has become an ideal target for the design of prodrug systems. This paper systematically reviews the types, characteristics and expression mechanism of base reducing enzymes in tumor tissues, describes in detail the design principle, structural types and latest research progress of these prodrug systems, deeply analyzes their application advantages and potential in tumor treatment, and discusses the current research bottle neck, so as to provide comprehensive theoretical reference and practical guidance for follow-up research in this field.